Defining and Achieving Freedom from Hunger: A Rights-Based Approach - Ghimire, Saurav (Kathmandu School of Law Review, 2013)
If one is born in the right part of the world and in right social class, the problem of being hungry has its solution in the nearest refrigerator. However, if the situation is reverse, one may go hungry throughout one’s short life, as 800million born in the wrong place and in wrong social class are doing as we discuss the concern. Peace cannot exist where the hunger prevails as the former signifies not merely the absence of armed conflict but the establishment of human rights for all people, and no human right is worth anything to a starving person. That is why the freedom from hunger is fundamental to live as human being and is a necessary part of right to life.